Mission to mach 2 a fighter pilot's memoir of supersonic flight - Haney, Robert Earl (McFarland, 2011)
The thirty-year period that marked the advent of the supersonic jet in military aviation was a particularly dangerous one for fighter pilots. As they learned to navigate speeds up to Mach 2, discovering the performance limits and weaknesses of the aircraft, their courage and stamina were tested to the limit. This engaging memoir relates the life story of a famed pilot who flew supersonic jets for the United States Air Force during the Cold War through Vietnam and beyond. As a test pilot, a member of the USAF Thunderbirds, a fighter pilot with more than 200 combat missions in the Vietnam War, and a Fighter Weapons School ("Top Gun") graduate and instructor, he was at the center of the most significant periods in military aviation.